Understanding catalysis - Roduner, Emil (Chemical Society reviews, 2014)
The large majority of chemical compounds underwent at least one catalytic step during synthesis. While it is common knowledge that catalysts enhance reaction rates by lowering the activation energy it is often obscure how catalysts achieve this. This tutorial review explains some fundamental principles of catalysis and how the mechanisms are studied. The dissociation of formic acid into H2 and CO2 serves to demonstrate how a water molecule can open a new reaction path at lower energy, how immersion in liquid water can influence the charge distribution and energetics, and how catalysis at metal surfaces differs from that in the gas phase. The reversibility of catalytic reactions, the influence of an adsorption pre-equilibrium and the compensating effects of adsorption entropy and enthalpy on the Arrhenius parameters are discussed. It is shown that flexibility around the catalytic centre and residual substrate dynamics on the surface affect these parameters. Sabatier's principle of optimum substrate adsorption, shape selectivity in the pores of molecular sieves and the polarisation effect at the metal-support interface are explained. Finally, it is shown that the application of a bias voltage in electrochemistry offers an additional parameter to promote or inhibit a reaction.